Study of Some Stages of Poliovirus Morphogenesis in MiO Cells - Ghendon, Y. (1972)
Five to seven minutes after addition of (14)C-amino acids to poliovirus-infected MiO cells, radioactivity is found only in 5S virus-specific structures. With increased time of labeling, radioactivity appears in considerable amounts also in the 14S area. In the presence of guanidine blocking the transition of 14S particles in subsequent structures in MiO cells, radioactivity is first detected in the 5S zone and then accumulates predominantly in 14S particles. These results indicate that formation of 5S particles and conversion of a part of their protein into 14S particles reflect the earliest stages of the morphogenesis of poliovirus. In contrast to poliovirus-infected HeLa cells, no 73S particles could be detected in MiO cells, nor could 73S structures be detected in poliovirus-infected MiO cells after a short incubation period (20 to 30 min) with radioactive amino acids, although formation of 150S virions was observed. Addition of guanidine to infected MiO cells leads to accumulation of 14S particles; however, 73S particles are not detected. After removal of guanidine, radioactivity increases only in the 150S area. Incubation of 14S particles isolated from the sucrose gradient of the cytoplasmic extract of infected MiO cells resulted in formation of 73S particles. The results obtained show the modification of the late stages of poliovirus morphogenesis in MiO cells.